Uji Coba Evaluasi Kinerja di PT Nikomas Gemilang Bagian Helper Divisi Nike Menggunakan Model Evaluasi Checklist - Shela Handayani; Sela Devi; Syamsul Hidayat (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to conduct a trial of employee performance evaluation of helper employees in the Nike Division of PT Nikomas Gemilang using a weighted checklist evaluation model. The research method used is descriptive research with data collection through observation, interviews, documentation, and performance checklist sheets. The research sample consisted of 5 helper employees in the Nike Division. The assessment instrument included 10 company performance indicators. The results showed that all respondents obtained the same total score of 100, indicating that all performance indicators had been met. The evaluation checklist model was considered simple, efficient, and easy to implement as an employee performance assessment tool. In addition, these results provide an illustration that the evaluation model can be applied in various other divisions to improve overall performance. In the future, the implementation of this weighted evaluation is expected to strengthen a work culture oriented towards achieving optimal results. This evaluation can also serve as a basis for development, training, and improvement of system performance in the future.